NASOPHARYNGEAL CARCINOMA IN PANYABUNGAN DISTRICT HOSPITAL - Pulungan, Muhammad Rusli (TALENTA PUBLISHER, 2020)
Abstract Introduction: Nasopharyngeal carcinoma is the most common malignancy found in the head and neck area. Non-specific initial symptoms and hidden locations often make it difficult to diagnose early nasopharyngeal carcinoma. The limitations of tools and human resources in the district are a problem in enforcing and finding patients with nasopharyngeal carcinoma in this situation. Objective: The purpose of this study is to observe the prevalence of nasopharyngeal carcinoma in Departement of Otorhinolaryngology-Head and Neck Surgery Panyabungan District Hospital. Method: This study collecting data from medical record of Nasopharyngeal carcinoma (NPC) at Panyabungan District Hospital. Result: The distribution of NPC patients during January-December 2018 there were 10 patients. NPC base on gender male 50% and female 50%. NPC based on age groups in 46-55 years is 40%, 56-65 years old is 20% and 16-25 years, 26-35 years, 36-45 years, and 66-75 years each of 10%. NPC patients based of clinical appearance is limadenophaty colli is 100%, epistaxis 80%, Nasal congesty 70%.ear fulness 40% and diplopia 30%. NPC based on histophatologycal types is WHO type I 10%, WHO type II 50% and WHO type III 40%.Â Conclusion: Nasopharyngeal carcinoma is a malignant tumor originating from the nasopharyngeal epithelium. The patient NPC were diagnosed at an advanced stage. All of patients showed enlargement of neck limph nodes and some showed diplopia.